Surge and pitch motion effects on aerodynamic performance of a spar floating offshore wind turbine under wave-wind loading (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The concerns over global warming and energy security have made the development and implementation of renewable energy a global priority. One notable renewable energy target is the 3X renewable energy program which aims to triple the renewable energy capacity before 2030 and almost 200 governments are committed to this program. Floating offshore wind turbines are one of a number of important sectors of this program with a set target of increasing 9% wind turbine installations annually over this period. Furthermore, the recent progress in this field shows the ability and ambitions of this industry to deliver on this long-term target. Due to the complex dynamics of floating offshore wind turbines, achieving this goal needs placing a huge focus on development, accurate simulations, and analysis of the operational performance of these structures in real conditions. Floating offshore wind turbines are frequently exposed to huge environmental loads which are wave, wind, and tidal/ocean current loads and the effect of the loads induce different motions with large amplitudes in 6-DOF. Among all the six degrees of freedom, surge and pitch motions have a significant effect on wind turbine rotor displacement and consequently on aerodynamic performance and power generation of floating offshore wind turbines. In this paper, the NREL 5-MW floating wind turbine supported by a spar platform is selected under wave-wind loading. Additionally, a fully-coupled analysis tool which is called F2A is utilised to provide a fully-coupled aero-hydro-servo-elastic simulation at a site along the Irish coastline. The F2A tool is open-source, efficient, and it provides a coupled simulation of hydrodynamic and aerodynamic loads with high degree of accuracy. The main aim of this paper is to present the finding of the analysis on the effects of surge and pitch motion on the aerodynamic performance and power generation, considering different wave-wind case simulations, and also to provide a detailed proposal for optimising the performance of these complicated platforms.